Evaluation of a self-administered oral glucose tolerance test. - Bethel, M; Price, H; Sourij, H; White, S; Coleman, R; Ring, A; Kennedy, I; Tucker, L; Holman, R (American Diabetes Association, 2013)
OBJECTIVE: To assess the feasibility of using a disposable, self-administered, capillary blood sampling oral glucose tolerance test (OGTT) device in a community setting. RESEARCH DESIGN AND METHODS: Eighteen healthy and 12 type 2 diabetic volunteers underwent six 75-g OGTTs using a prototype device in the following three settings: unaided at home (twice); unaided but observed in clinic (twice); and performed by a nurse with simultaneous laboratory glucose assays of 0- and 120-min venous plasma samples (twice). The device displayed no results. A detachable data recorder returned to the clinic provided plasma-equivalent 0- and 120-min glucose values and key parameters, including test date, start and end times, and time taken to consume the glucose drink. RESULTS: The device was universally popular with participants and was perceived as easy to use, and the ability to test at home was well liked. Device failures meant that 0- and 120-min glucose values were obtained for only 141 (78%) of the 180 OGTTs performed, independent of setting. Device glucose measurements showed a mean bias compared with laboratory-measured values of +0.9 at 5.0 mmol/L increasing to +4.4 at 15.0 mmol/L. Paired device glucose values were equally reproducible across settings, with repeat testing showing no training effect regardless of setting order. CONCLUSIONS: Self-administered OGTTs can be performed successfully by untrained individuals in a community setting. With improved device reliability and appropriate calibration, this novel technology could be used in routine practice to screen people who might need a formal OGTT to confirm the presence of impaired glucose tolerance or diabetes.